Influence of the thought Process on the Emotional Component of the Performing Activity of a Music Institution Student - Vladimirovna Pavlova, Natalia (International Journal of Psychosocial Rehabilitation, 2020)
At the present stage of development of music education, the integrity of the performance of a music institution student is a science of educating and training a person in the unity of theory and practice, combining a special, intellectual, and emotional component. The relevance of the correlation of the intellectual-mental and emotional component in the study of the performance of a music institution student is unquestionable, as the training of specialist music high school involves the formation and development of the competitive ability of the specialist to demonstrate their knowledge, skills, and practice-confirmed theory. The very mechanism of the human brain has long been considered the most difficult problem in science. In the last decade, because of scientific and technological progress, more and more complex human intellectual abilities have begun to manifest. Most studies of the relationship between intellectual-mental and emotional components are aimed at developing combinations of emotions and reason in the theoretical understanding of human activity. Performing activities of a music institution student expand this theoretical framework. Within the framework of performing activities, a music institution student can learn, acquiring new knowledge and implementing it in practice. In the performance activity of a music institution student, the composer's idea is realized in the interrelation of intellectual, mental, and emotional relations. Thus, the synthesis of the musical aspects of performing, the personality of the student by her characteristics (ability, emotionality, temperament and character, mindset, motivation, etc.), and intellectual-mental processes that promote the formation of objective criteria and indicators of the performance of a music institution student as a whole.